Exosomes from high-altitude cerebral edema patients induce cognitive dysfunction by altering oxidative stress responses in mice - Qiang Fu; Rui Qiu; Quan Tang; Xiaodong Li; Yaobo Li; Yuxiang Qin; Qiaosheng Li; Jia Yao; Zhongyong Jiang; Huan Xu; Yong Cheng (Translational Psychiatry)
Abstract The impact of exosomes derived from patients with High Altitude Cerebral Edema (HACE) on cognitive function in mice was investigated, along with the underlying mechanisms. Exosomes were extracted from HACE patients and injected into the dentate gyrus (DG) of mice. A series of behavioral tests assessed cognitive abilities. Results indicated that mice injected with HACE patient exosomes exhibited significant declines in exploratory behavior and object recognition, suggesting notable cognitive impairments. Additionally, these exosomes induced oxidative stress responses and abnormal activation of microglia, closely associated with neuronal death. Proteomic analysis revealed that the differentially expressed protein STAMBP, which is closely linked to neurodevelopment, may play a key role. In conclusion, our findings highlight the potential impact of exosomes from HACE patients on cognitive dysfunction in mice, providing new insights into the pathophysiological mechanisms of HACE.